Oral Health Awareness among International Dental and Medical Students at Lithuanian University of Health Sciences: a Cross-Sectional Study - Sandra Petrauskiene; Hava Mushayev; Gintare Zemgulyte; Julija Narbutaite (Stilus Optimus, 2019)
Objectives: To evaluate the self-reported oral health awareness, knowledge and attitude among international dental and medical students at the Lithuanian University of Health Sciences (Kaunas, Lithuania). Material and Methods: A cross-sectional study was conducted among international medical and dental students at the Lithuanian University of Health Sciences in 2016 - 2017. The students were invited to participate in the survey before the beginning of a lecture, and they were informed that participation was voluntary and anonymous. In total, 282 students participated in the study, with a response rate of 92.1%. A self-administered English questionnaire consisting of 25 items with options on a Likert scale (agree, neither agree nor disagree and disagree) about oral health problems and their relation to general health status was used to assess a student's oral health awareness, attitude and knowledge. The level of significance was set at P < 0.05. Results: Overall good, fair and poor oral health awareness was reported by 71.3%, 24.1% and 4.6%, respectively, of the international dental and medical students (P < 0.05). The mean score of oral health awareness was 18.2 (standard deviation [SD 3.27]), showing overall good oral health awareness. Moreover, the international dental students reported higher oral health awareness than medical students (19.14 [SD 3.25] vs 17.44 [SD 3.1]) (P < 0.001). Comparing this mean score by gender, no statistically significant difference was found (18.33 [SD 3.39] vs 18.05 [SD 3.16]) (P = 0.371). Conclusions: Overall oral health awareness among international dental and medical students was high. Meanwhile, international dental students reported higher oral health awareness than international medical students.